Development of a Colloidal Gold-Based Immunochromatographic Strip for Rapid Detection of H7N9 Influenza Viruses - Sun, Zhihao; Shi, Baolan; Meng, Feifei; Ma, Ruonan; Hu, Qingyun; Qin, Tao; Chen, Sujuan; Peng, Daxin; Liu, Xiufan (Frontiers in Microbiology, 2018)
Both high- and low-pathogenic H7N9 influenza A virus (IAV) infections have been found in human and poultry in China, and most human cases are related to contact with infected poultry. It is necessary to develop a rapid and simple method to detect H7N9 IAV in poultry. In this study, 13 monoclonal antibodies (McAbs) against the H7N9 IAV hemagglutinin were developed, and three critical amino acid epitopes (198, 227, 235) were identified based on the reactivity of these variant and wild-type strains with the McAbs. We developed an immunochromatographic assay for H7N9 AIVs using two McAbs recognizing the epitope position 227 and 235. The assay had good specificity, stability, and sensitivity, with a detection limit of swab and tissue samples of 2.5 log10EID50/0.1 mL, which is suitable for the analysis of clinical samples. This assay provides an effective method for the rapid detection of H7N9 AIVs in poultry.